Novel Regulatory Factors and Small-Molecule Inhibitors of FGFR4 in Cancer - Liu, Yanan; Wang, Canwei; Li, Jifa; Zhu, Jiandong; Zhao, Chengguang; Xu, Huanhai (Frontiers in Pharmacology, 2021)
Fibroblast growth factor (FGF) receptor 4 (FGFR4) is a tyrosine kinase receptor that is a member of the FGFR family and is stimulated by highly regulated ligand binding. Excessive expression of the receptor and its ligand, especially FGF19, occurs in many types of cancer. Abnormal FGFR4 production explains these cancer formations, and therefore, this receptor has emerged as a potential target for inhibiting cancer development. This review discusses the diverse mechanisms of oncogenic activation ofFGFR4, and highlights some currently available inhibitors targeting FGFR4.